Partitioning of energy intake in broiler breeders from 27 to 63 weeks old - Teofilo, Guilherme Ferreira da Silva [UNESP]; Morillo, Freddy Alexander Horna [UNESP]; Kareem, Damilola Uthman [UNESP]; Lizana, Rony Riveros [UNESP]; Bonagurio, Lucas Pimentel [UNESP]; Camargos, Rosiane de Souza [UNESP]; Van Milgen, Jacob; Macari, Marcos [UNESP]; Sakomura, Nilva Kazue [UNESP] (Elsevier, 2024)
Describing the energy partition during the production phase of broiler breeders helps to define the energy requirements of breeders. This study aimed to determine the energy intake partition for maintenance, tissue growth, and egg production in broiler breeders during the laying phase. An energy and nitrogen balance study was carried out in a respirometry chambers with fifty Cobb 500 broiler breeders from 27 to 63 weeks old. Every four weeks, 5 birds were individually housed in a respirometry chamber and fed according to the guidelines. Feed intake (FI), excreta, and egg output were recorded daily. O2 consumption (VO2) and CO2 production (VCO2) were measured under feeding and fasting conditions to calculate total and fasting heat production (THP and FHP, respectively). The collected data were used to calculate the retained energy (RE) in the egg and body as protein or fat by using energy balance calculations. Linear regressions were used to fit the collected data as a function of age. The measured apparent metabolizable energy corrected for zero-nitrogen retention (AMEn, kJ/kg feed) was higher than formulated. The FI and apparent metabolizable energy intake (AMEi) showed the highest values at 31 and 35 weeks (P > 0.05). Linear regression was not significant (P > 0.05) for FHP, THP, heat increment (HI), egg mass, and RE in the egg as fat and as protein, suggesting that these parameters remained constant as the bird aged. The RE in the body as protein increased (P < 0.005), while the RE in the body as fat decreased (P < 0.0001) as the birds aged. Variation in the AMEi influenced RE in the body (P < 0.05) but not in the egg (P = 0.109). It can be concluded that net energy for maintenance does not change during the laying phase and represents an expenditure of 267.1 kJ/kg0.75 per day in broiler breeders under a feed-controlled program. As expected, energy is primarily used for maintenance and egg production in the net energy system, with excess energy stored preferentially as fat rather than protein.
Keywords: Body composition; Energy balance; Energy system; Fasting heat production; Indirect calorimetry